2022
DOI: 10.1021/jacs.1c12335
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Assembly as a Materials Development Tool

Abstract: Nanoparticle assembly is a complex and versatile method of generating new materials, capable of using thousands of different combinations of particle size, shape, composition, and ligand chemistry to generate a library of unique structures. Here, a history of particle self-assembly as a strategy for materials discovery is presented, focusing on key advances in both synthesis and measurement of emergent properties to describe the current state of the field. Several key challenges for further advancement of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 190 publications
0
64
0
Order By: Relevance
“…However, several long-term challenges remain (or just emerge) to bring these fundamental insights from the lab to actual applications. These include the upscaling of films toward largescale (>>µm 2 ) homogeneous assemblies, [39,311] device integration or combination with traditional bulk materials, [312] and automatization of film fabrication. To master these challenges will decide on the transfer of materials based on assemblies of colloidal nanoparticles to large scale applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, several long-term challenges remain (or just emerge) to bring these fundamental insights from the lab to actual applications. These include the upscaling of films toward largescale (>>µm 2 ) homogeneous assemblies, [39,311] device integration or combination with traditional bulk materials, [312] and automatization of film fabrication. To master these challenges will decide on the transfer of materials based on assemblies of colloidal nanoparticles to large scale applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are emergent mechanical properties of colloidal crystals provided by their ordering nature compared to those of amorphous colloidal assemblies. 14 In our previous study, we observed that DNA–AuNP crystals tend to maintain their single-crystal polyhedral shapes through the drying process. 15,16 However, DNA-functionalized colloidal crystallization for molecular encapsulation has rarely been studied.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, the assembly of metal NPs shows unique optical, electronic, and magnetic properties that can be engineered for many technological uses. [14][15][16][17][18][19][20] Therefore, the ability to control the assembly of NPs not only is required for many real technological applications, but allows the combination of the intrinsic properties of NPs and opens the way to the exploitation of their complex interplay, giving full access to collective properties. In light of this, the assembly of NPs has been extensively addressed, both from the viewpoints of laboratory work and computational simulations.…”
Section: Introductionmentioning
confidence: 99%